Mechanochemical synthesis of yttrium manganite - Počuča-Nešić, M.; Marinković Stanojević, Z.; Branković, Z.; Cotič, P.; Bernik, S.; Góes, M. Sousa [UNESP]; Marinković, B. A.; Varela, José Arana [UNESP]; Branković, G. (Elsevier, 2013)
Yttrium manganite (YMnO3) is a multiferroic material, which means that it exhibits both ferromagnetic and ferroelectric properties, so making it interesting for a variety of technological applications. In this work, single-phase YMnO3 was prepared for the first time by mechanochemical synthesis in a planetary ball mill. The YMnO3 was formed directly from the highly activated constituent oxides, Y 2O3 and Mn2O3, after 60 min of milling time. During prolonged milling, the growth of the particles occurred. The cumulative energy introduced into the system during milling for 60 min was 86 kJ/g. The X-ray powder-diffraction analysis indicates that the as-prepared samples crystallize with an orthorhombic (Pnma) YMnO3 structure. The morphology and chemical composition of the powder were investigated by SEM and FESEM. The magnetic properties of the obtained YMnO3 powders were found to change as a function of the milling time in a manner consistent with the variation in the nanocomposite microstructure. © 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic properties; Mechanochemistry; Microstructure; Multiferroic materials; Yttrium manganite; Chemical compositions; Cumulative energy; Ferroelectric property; Mechano-chemistry; Mechanochemical synthesis; Milling time; Nanocomposite microstructure; Planetary ball mill; Technological applications; Yttrium manganites; Ball mills; Manganese oxide; Milling (machining); Yttrium; Yttrium alloys